Pengaruh Profitabilitas, Kualitas Auditor, dan Reaksi Pasar tehadap Ketepatan Waktu Pelaporan Keuangan Pada Perusahaan Manufaktur Terindeks Lq 45 - Suriani Suriani; Agussalim Rahman (STIE AMKOP, 2023)
This study aims to determine the effect of profitability, auditor quality, and market reaction on the timeliness of financial reporting in LQ 45 indexed manufacturing companies for the 2019-2020 period. This type of research is a quantitative study with a total sample of 22 manufacturing companies indexed by LG45 and data analysis using multiple linear regression data analysis. The results of the study show that there is an influence on Profitability, Auditor Quality, and Market Reaction to the Timeliness of Financial Reporting in LQ 45 Indexed Manufacturing Companies for the 2019-2020 period. Keywords: Profitability, Auditor Quality, Market Reaction, Timeliness of Reporting